Exemplar‐Based Portrait Photograph Enhancement as Informed by Portrait Paintings. (13th June 2014) - Zhang, Xiaoyan; Constable, Martin; Chan, Kap Luk
<x xml:space="preserve">Abstract</x> This paper proposes an approach to enhance the regional contrasts in snap‐shot style portrait photographs by using pre‐modern portrait paintings as aesthetic exemplars. The example portrait painting is selected based on a comparison of the existing contrast properties of the painting with those of the photograph. The contrast organization in the selected example painting is transferred to the photograph by mapping the inter‐ and intra‐regional contrasts of the regions, such as the face and skin areas of the foreground figure, the non‐face/skin part of the foreground, and the background region. A piecewise nonlinear transformation curve is used to achieve the contrast mapping. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>